Ulerythema ophryogenes (keratosis pilaris atrophicans faciei). - Ferrara, M. (European Journal of Pediatric Dermatology, 2016)
Ulerythema ophryogenes (UO) is an inherited disorder of keratinization that usually manifests in the form of sporadic cases. It can be present at birth or begin in early stages of life. UO is characterized by keratosis pilaris, thinning and inflammation of the eyebrows. The severe disorder of keratinization results in the formation of a keratin plug in the hair follicle that is responsible for thinning of the hairs; the penetration of the hair in the hair follicle wall blocked by keratin would be responsible for the inflammation resulting in scarring alopecia. UO may be associated with atopy as in our case and with many hereditary diseases, especially Noonan syndrome (2, 3). Emollients, vitamin A, topical and systemic retinoids are substantially ineffective; erythema transiently responds to topical corticosteroids; the dye laser is effective on erythema in some cases (1).